Vous êtes sur la page 1sur 9

3k + 2 k + 1

Example 4 : Solve the equation =


2k + 5 k − 1
3k + 2 k + 1
Consider =
2k + 5 k − 1
Cross multiplying (3k + 2) (k – 1) = (2k + 5) (k + 1)
3k2 + 2k – 3k – 2 = 2k2 + 5k + 2k + 5
3k2 – 1k – 2 – 2k2 – 7k – 5 = 0
3k2 – 1k – 2 – 2k2 – 7k – 5 = 0
On simplification k2 – 8k – 7 = 0
This is in form of ax2 + bx + c = 0
The co-efficients are a = 1, b = –8, c = –7

− b + (− b) 2 − 4ac
The roots of the equation x=
2a

− (−8) ± (−8) 2 − 4(1)(−7)


∴ k =
2 x1
+ 8 ± 64 + 28
∴ k =
2

8 ± 92
k =
2

k =
8 ± 2 23
=
(
2 4 ± 23 )
2 2
k = 4 ± 23

y 3
Example 5 : Solve the equation − =1
4 2y
y 3
Consider − =1
4 2y

y2 − 6
Taking L.C.M. =1
4y
By cross multiplication y2 – 6 = 4y
y2 – 4y – 6 = 0

135
this is in the form ax2 + bx + c = 0
comparing coefficients a = 1, b = –4, c = –6

− (−4) ± (−4) 2 − 4(1)(−6)


y =
2(1)

4 ± 16 + 24
the roots of the equation are =
2
4± 40
y =
2

y =
4 ± 2 10
=
(
2 2 ± 10 )
2 2
y = 2 + 10 or y = 2 − 10

4 1 4
Example 6 : Solve − =
m + 2 m + 3 2m + 1
4(m + 3) − 1(m + 2) 4
=
(m + 2)(m + 3) 2m + 1
4m + 12 − m − 2 4
=
m + 2m + 3m + 6 2m + 1
2

3m + 10 4
=
m + 5m + 6 2 m + 1
2

On Cross multiplying, 4m2 + 20m + 24 = 6m2 + 20m + 3m + 10


4m2 + 20m + 24 – 6m2 – 23m – 10 = 0
–2m2 – 3m + 14 = 0
This is in the Standard form 2m2 + 3m – 14 = 0
2m2 + 7m – 4m – 14 = 0
m(2m + 7) –2 (2m + 7) = 0
(2m + 7) (m – 2) = 0
Either (2m + 7) = 0 or (m – 2) = 0

−7
m= or m=2
2

136
mn =
(
b 2 − b 2 − 4ac )
4a 2
b 2 − b 2 + 4ac
mn =
4a 2
4ac c c
∴ mn = 2 = ∴ mn =
4a a a

Example 1 : Find the sum and product of the roots of equation x2 + 2x + 1 = 0


x2 + 2x + 1 = 0
This is in the form ax2 + bx + c = 0
The coefficients are a = 1, b = 2, c = 1
Let the roots be m and n

−b −2
i) Sum of the roots m + n = =
a 1
∴ m + n = –2

c 1
ii) Product of the roots mn = =
a 1
∴ mn = 1

Example 2 : Find the sum and product of the roots of equation 3x2 + 5 = 0
3x2 + 0x + 5 = 0
This is in the form ax2 + bx + c = 0
The coefficients are a = 3, b = 0, c = 5
Let the roots are p and q

−b 0
i) Sum of the roots p + q = =
a 3
∴ p+q = 0

c 5 5
ii) Product of the roots pq = = ∴ pq =
a 3 3

147
Example 3 : Find the sum and product of the roots of equation 2m2 – 8m = 0
2m2 – 8m + 0 = 0
The coefficients are a = 2, b = –8, c = 0
Let the roots be α and β
−b − (−8)
i) Sum of the roots α+β = = = 4
a 2
c 0
ii) Product of the roots αβ = = = 0
a 2

Example 4 : Find the sum and product of the roots of equation x2 – (p+q)x + pq = 0
x2 – (p + q) x + pq = 0
The coefficients are a = 1, b = –(p + q), c = pq
−b
i) Sum of the roots m + n =
a
− [− (p + q )]
m + n =
1
∴ m + n = (p + q)

c pq
ii) Product of the roots mn = =
a 1
∴ mn = pq

Exercise : 5.7
Find the sum and product of the roots of the quadratic equation :
1) x2 + 5x + 8 = 0 2) 3a2 – 10a – 5 = 0 3) 8m2 – m = 2
4) 6k2 – 3 = 0 5) pr2 = r – 5 6) x2 + (ab) x + (a + b) = 0

8. To form an equation for the given roots


Let ‘m’ and ‘n’ are the roots of the equation
∴ x = ‘m’ or x = ‘n’
i.e., x – m = 0, x – n = 0
(x – m) (x – n) = 0
∴ x2 – mx – nx + mn = 0
x2 – (m + n) x + mn = 0

148
Exercise : 5.8
A. Form the equation whose roots are
3 2 3
1) 3 and 5 2) 6 and –5 3) –2 and 4) and
2 3 2
5) 2 + 3 and 2 – 3 6) –3 + 2 5 and –3 – 2 5

B.
1) If ‘m’ and ‘n’ are the roots of the equation x2 – 6x + 2 = 0 find the value of
1 1
i) (m + n) mn ii) +
m n

2) If ‘a’ and ‘b’ are the roots of the equation 3m2 = 6m + 5 find the value of
a b
i) + ii) (a + 2b) (2a + b)
b a

3) If ‘p’ and ‘q’ are the roots of the equation 2a2 – 4a + 1 = 0 Find the value of
i) (p + q)2 + 4pq ii) p3 + q3
p q
4) Form a quadratic equation whose roots are and
q p
5) Find the value of ‘k’ so that the equation x2 + 4x + (k + 2) = 0 has one root equal
to zero.
6) Find the value of ‘q’ so that the equation 2x2 – 3qx + 5q = 0 has one root which
is twice the other.
7) Find the value of ‘p’ so that the equation 4x2 – 8px + 9 = 0 has roots whose
difference is 4.
8) If one root of the equation x2 + px + q = 0 is 3 times the other prove that 3p2 = 16q

Graphical method of solving a Quadratic Equation


Let us solve the equation x2 – 4 = 0 graphically,
x2 – 4 = 0
∴ x2 = 4
let y = x2 = 4
∴ y = x2
and y = 4

153
Step 1: Form table of
corresponding values y = x2
of x and y x=0 y = 02 y=0
Satisfying the equation x=1 y = 12 y=1
y = x2 x=2 y = 22 y=4
Step 2: Choose the scale on x = –1 y = (–1)2 y=1
x axis, 1 cm = 1 unit x = –2 y = (–2)2 y=4
y axis, 1 cm = 1 unit.
Step 3: Plot the points (0, 0);
(1, 1); (–1, 1); (2, 4)
and (–2, 4) on graph
sheet.
Step 4: Join the points by a
smooth curve.
Step 5: Draw the straight line
y = 4 Parallel to x-axis
Step 6: From the intersecting
points of the curve and
the line y = 4, draw
perpendiculars to the
x axis
Step 7: Roots of the equations are x = +2 or x = –2

The graph of a quadratic polynomial is a curve called ‘parabola’

Example 1 : Draw a graph of y = 2x2 and find the value of 3 , using the graph.
Step 1: Form the table of
corresponding values of
x and y satisfying the
equation y = 2x2
Step 2: Choose the scale on x x 0 1 –1 2 –2 3
y 0 2 2 8 8 6
axis, 1 cm = 1 unit and
(x, y) (0, 0) (1, 2) (–1, 2) (2, 8) (–2, 8) ( 3 ,6)
y axis, 1 cm = 1 unit
Step 3: Plot the points (0, 0);
(1, 2) (–1, 2); (2, 8) and
(–2, 8) on graph sheet.

154
Step 4: Join the points by a
smooth curve

Step 5: Draw the straight line


y = 6 Parallel to x-axis.

Step 6: From the intersecting


points of the curve and
the line y = 6, draw
perpendiculars to the
x-axis.

Step 7: Value of 3 = ± 1.7


x = –1.7 or x = + 1.7

Example 2 : Draw a graph of y = x2 and y = 2-x and hence solve the equation
x2 + x – 2 = 0
Step 1: Form the table of x 0 1 –1 2 –2
corresponding values of y 0 1 1 4 4
x and y satisfying the (x, y) (0, 0) (1, 1) (–1, 1) (2, 4) (–2, 4)
equation y = x2
x 0 1 –1 2 –2
Step 2: Form the table of
corresponding values of y 2 1 3 0 4
x and y satisfying the (x, y) (0, 2) (1, 1) (–1, 3) (2, 0) (–2, 4)
equation y = 2 – x.
Step 3: Choose the scale on x
axis 1 cm = 1 unit and
y axis, 1 cm = 1 unit.
Step 4: Plot the points (0, 0);
(1, 1); (–1, 1); (2, 4)
and (–2, 4) on the graph
sheet.
Step 5: Join the points by a
smooth curve.
Step 6: Plot the points (0, 2) ;
(1, 1); (–1, 3); (2, 0)
and (–2, 4) on graph
sheet
155
Step 7: Join the points to get a line.
Step 8: From the intersecting
Curve and the line, draw
perpendiculars to the
x-axis
Step 9: Roots of the equation are ∴ x = 1 or x = –2

Example 3 : Solve the equation


Method I : x2 – x – 2 = 0 x 0 1 –1 2 –2

Split the equation y 2 1 1 4 4

y = x2 and y = 2 + x (x, y) (0, 0) (1, 1) (–1, 1) (2, 4) (–2, 4)

Step 1: Form the table of


corresponding values x
and y satisfying the x 0 1 2 –1 –2
equation y = x2 y 2 3 4 1 0
Step 2: Form the table of (x, y) (0, 2) (1, 3) (2, 4) (–1, 1) (–2, 0)
corresponding values x
and y satisfying the
equation y = 2 + x
Step 3: Choose the scale on
x axis, 1 cm = 1 unit
y axis, 1 cm = 1 unit
Step 4: Plot the points (0, 0);
(1, 1); (–1, 1); (2, 4)
and (–2, 4) on the graph
sheet.
Step 5: Join the points by a
smooth curve
Step 6: Plot the points (0, 2);
(1, 3) (2, 4); (–1, 1) and
(–2, 0) on the graph
sheet.
Step 7: Join the points to get a
straight line
Step 8: From the intersecting
points of Curve and the
line, draw the perpendi-
culars to the x-axis.
Step 9: Roots of the equation are x = –1 or x = 2

156
Method II : x 0 1 –1 2 –2
Step 1: Form the table of y –2 –2 0 0 4
corresponding values of (x, y) (0, –2) (1, –2) (–1, 0) (2, 0) (–2, 4)
x and y satisfying
equation y = x2 – x – 2.
Step 2: Choose the scale on x
axis 1 cm = 1 unit and
y axis 1 cm = 1 unit.
Step 3: Plot the points (0, –2);
(1 –2); (–1, 0); (2, 0)
and (–2, 4) on the graph
sheet.
Step 4: Join the points to form
a smooth curve
Step 5: Mark the intersecting
points of the curve and
the x – axis.
Step 6: Roots of the equations are x = –1 or x = 2

Exercise : 5.9
A. 1) Draw the graph of y = x2 and find the value of 7
2) Draw the graph of y = 2x2 and find the value of 3
1 2
3) Draw the graph of y = x and find the value of 10
2
B. 1) Draw the graph of y = x2 and y = 2x + 3 and hence solve the equation
x2 – 2x – 3 = 0
2) Draw the graph of y = 2x2 and y = 3 – x and hence solve the equation
2x2 + x – 3 = 0
3) Draw the graph of y = 2x2 and y = 3 + x and hence solve the equation
2x2 – x – 3 = 0

C. Solve graphically
1) x2 + x – 12 = 0 2) x2 – 5x + 6 = 0 3) x2 + 2x – 8 = 0
4) x2 + x – 6 = 0 5) 2x2 – 3x – 5 = 0 6) 2x2 + 3x – 5 = 0

157

Vous aimerez peut-être aussi